Edukasi Stunting melalui Emo Demo “Camilan O’ke” pada Ibu Balita di Desa Bulak, Rowosari, Kendal - Nafilah; Ardian Candra Mustikaningrum; Eliyana; Ananda Desfa Syahrani; Angela Putri Aprilliani (LPPM Akbid Harapan Ibu Pekalongan, 2025)
Stunting in toddlers is still a special concern, especially in Kendal Regency. One of the causes of stunting is the mother's knowledge about providing inappropriate complementary feeding. In fact, Kendal Regency has local food ingredients in the form of mackerel which is an alternative to prevent stunting. Therefore, it is necessary to increase the mother's knowledge about the use of local food sources in preventing stunting. The purpose of this Community Service activity is to increase knowledge by providing Stunting Education through the